Reforming public services in India : drawing lessons from success (SAGE Publications, 2020)
Introduction -- Promoting competition -- India's Telecom revolution -- Competition in marketing services to farmers: ITC's e-choupal -- Conclusion -- Simplifying transactions -- One-stop service centres -- Andhra Pradesh's eseva model -- Kerala's friends programme -- Computerisation of land records in Karnataka -- Some challenges in the implementation of e-governance -- Gujarat's computerised interstate check-posts -- Andhra Pradesh's card -- Conclusion -- Restructuring agency processes -- Statewide agencies -- The registration department in Maharashtra -- The Karnataka State Road Transport Corporation -- City agencies -- The Hyderabad Metropolitan Water Supply and Sewerage Board -- Bangalore: making city agencies work? -- Surat after the plague, 1994-2005 -- Conclusion -- Decentralising teacher management -- The Madhya Pradesh experience -- Conclusion -- Building political support for programme delivery -- Comparing human development outcomes: Tamil Nadu vs Karnataka, 1971-2001 -- Conclusion -- Strengthening accountability mechanisms -- Civil service reform: transfers in Karnataka -- Unveiling secrets: access to information in Rajasthan, Delhi and Karnataka -- Anti-corruption institutions -- The Karnataka Lokayukta -- The central vigilance commission -- Public interest litigation -- Conclusion -- Lessons for improving service delivery -- The enabling environment -- Instruments for improving service delivery -- Cross-cutting issues -- Conclusion: learning from success.